2014
DOI: 10.1039/c4sc00948g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced H-bonding and π-stacking in DNA: a potent duplex-stabilizing and mismatch sensing nucleobase analogue

Abstract: Combining enhanced π-stacking, H-bonding and electrostatic attraction in a single C-monomer greatly increases DNA duplex stability and massively destabilises mismatches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 50 publications
(66 reference statements)
1
22
0
Order By: Relevance
“…7,8 The C4 chloro derivatives can be prepared by one of two methods, either chlorination with SOCl 2 /DMF, 912 or via the Appel reaction with PPh 3 /CCl 4 . 13–15 However, such chloro compounds seem labile 16 and have been used immediately upon preparation. For instance, the C4 chloro derivatives were converted to the C4 ethoxy compounds, which were then used in displacement reactions with nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The C4 chloro derivatives can be prepared by one of two methods, either chlorination with SOCl 2 /DMF, 912 or via the Appel reaction with PPh 3 /CCl 4 . 13–15 However, such chloro compounds seem labile 16 and have been used immediately upon preparation. For instance, the C4 chloro derivatives were converted to the C4 ethoxy compounds, which were then used in displacement reactions with nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
“…10 More recently, it has been shown that the presence of additional side-groups that enhance p-stacking interactions greatly improves the selectivity of a novel nucleobase analogue for its complementary DNA partner. 11 It is therefore important, for promoting hybridization with nucleic acids, to develop synthetic methodologies that enable the construction of biomolecular conjugates featuring functionalized nucleobases tethered to an organic scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Specific examples of pyrene-modified oligonucleotides reviewed here include sensitive fluorescent probes for the sequence-specific detection of nucleic acids (NAs) and discrimination of single nucleotide polymorphisms (SNPs), aptamer-based biosensors for the detection of a wide range of various targets, agents for binding of dsDNAs, building units of supramolecular complexes, and other applications. These simple synthetically-accessible molecules integrate an excellent recognition capability of oligonucleotides and ability of pyrene to act as microenvironment-sensitive fluorescent label [ 1 , 2 , 3 , 4 ], excimer- or exciplex-generating molecule [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], NA complex intercalator [ 16 , 17 , 18 , 19 ], or π-π-staking hydrophobic moiety [ 20 , 21 ]. It is worth noting that these functions of pyrene are especially brightly expressed in the NA context.…”
Section: Introductionmentioning
confidence: 99%